PERANAN SALEH DJASIT DALAM PEMBANGUNAN PROVINSI RIAU TAHUN 1998-2003 - Khori Pilihan; Isjoni '; Bunari ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrak :Djasit in Riau Province development. 3. To know us faktor endowments and the factors resricting Saleh Djasit le aders in Riau Province. In this study usig the method of qualitative and h: The purpose of the research was 1. To know the life of Saleh Djasit. 2. To know the role of Saleh istorical. Methods of qualitative research is about reseaarch that is both descriptive and tend to use analysis. Historical research is a way of revealing the back past events or research live of Saleh Djasit childhood, education and adolescence. The construction of mosques kingdom great an-nur Pekanbaru. Regional general Hospital/hospital arifin acmad Pekanbaru. Technological boarding school. Kaharuddin Nastion stadium. Politehnic Caltex. Artpavilion indrus tintin. Faculty of medicine og the University of Riau and Riau Plus high school. Supporting factors and the factors restricting Saleh Djasit Provincial leaders in Riau.Keywords: The Role, Saleh Djasit, in the development of Riau Province.